2017
DOI: 10.1182/blood-2016-09-741611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of unipotent megakaryocyte progenitors in human hematopoiesis

Abstract: The developmental pathway for human megakaryocytes remains unclear, and the definition of pure unipotent megakaryocyte progenitor is still controversial. Using single-cell transcriptome analysis, we have identified a cluster of cells within immature hematopoietic stem- and progenitor-cell populations that specifically expresses genes related to the megakaryocyte lineage. We used CD41 as a positive marker to identify these cells within the CD34CD38IL-3RαCD45RA common myeloid progenitor (CMP) population. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 39 publications
5
43
2
1
Order By: Relevance
“…The CD41 + fraction of human CD38 + CD34 + lin -CD45RA -HSPCs contains megakaryocyte-biased progenitors with significant erythroid differentiation potential as well as unipotent MkP (Miyawaki et al, 2017;Psaila et al, 2016). However, the phenotype of CD41 + cells within the CD38 -HSC/MPP compartment has not previously been defined.…”
Section: Analysis Of Mobilized Hspcs Demonstrates Megakaryocyte-biasementioning
confidence: 99%
“…The CD41 + fraction of human CD38 + CD34 + lin -CD45RA -HSPCs contains megakaryocyte-biased progenitors with significant erythroid differentiation potential as well as unipotent MkP (Miyawaki et al, 2017;Psaila et al, 2016). However, the phenotype of CD41 + cells within the CD38 -HSC/MPP compartment has not previously been defined.…”
Section: Analysis Of Mobilized Hspcs Demonstrates Megakaryocyte-biasementioning
confidence: 99%
“…Even though CD34+CD38high human cells have been published as being greatly enriched for erythroid committed cells,[10] papers still use this gate to isolate what they refer to as human “MEP.” Consequently, single cell RNA sequencing data from this population shows that many of these cells are erythroid committed, which would lead investigators to question the existence of human MEPs. [27, 28]…”
Section: Challenges In Isolating Mepmentioning
confidence: 99%
“…Recently, it was shown that MKPs could be generated directly from a subset of CD41 + LSK (Lin − Sca‐1 + c‐Kit + ) cells bypassing megakaryocyte‐erythrocyte progenitors (MEPs) in mice (Nishikii et al , ). More recently, Miyawaki et al () identified a unipotent MKP within the CD34 + CD38 + IL‐3Rα dim CD45RA – common myeloid progenitor (CMP) population in humans by using CD41 as a positive marker. These CD34 + CD38 + IL‐3Rα dim CD45RA – CD41 + CMPs (CD41 + CMPs) were strictly committed to the megakaryocyte (MK) lineage, and their potential to produce megakaryocytes and platelets far exceeded that of the MEPs (Miyawaki et al , ).…”
Section: Megakaryocytopoiesismentioning
confidence: 99%
“…More recently, Miyawaki et al () identified a unipotent MKP within the CD34 + CD38 + IL‐3Rα dim CD45RA – common myeloid progenitor (CMP) population in humans by using CD41 as a positive marker. These CD34 + CD38 + IL‐3Rα dim CD45RA – CD41 + CMPs (CD41 + CMPs) were strictly committed to the megakaryocyte (MK) lineage, and their potential to produce megakaryocytes and platelets far exceeded that of the MEPs (Miyawaki et al , ). Therefore, the expression of CD41 begins at the HPC (mouse) or CMP (human) stage and the expression of CD42b begins at the MKP stage during megakaryocytopoiesis (Woolthuis & Park, ).…”
Section: Megakaryocytopoiesismentioning
confidence: 99%